THE IMPACT OF OPEN EDUCATIONAL RESOURCES (OERS) AS EDUCATIONAL TOOL FOR EMERGING TECHNOLOGIES IN THE AGRICULTURE SECTOR - Pardiñan, Eric G (Journal of Agriculture and Technology Management, 2022)
Textbooks account for a significant chunk of college student's tuition costs, which are a vital part of their education. Web-based teaching and learning have become increasingly popular due to the Internet's immense reach and the ease with which technology may be used. Hence, the study focused on the impact of Open Educational Resources (OERs) on emerging technologies in the agricultural sector. The paper utilized the descriptive- correlation method research design. The study uses closed-ended questions to collect data that helps draw objective conclusions that help derive patterns, respondents' traits, and behaviors on the impact of incorporating technologies. The survey questionnaire would be utilized to gather needed information as the basis for correlation analysis to determine the relationship between the use of Open Educational Resources and the respondents' academic performance. The Chi-Square test of Independence and Pearson correlation are the statistical tests used to analyze the significant association between students' academic achievement and their perception of the Internet. The paper revealed that OERs keep students interested and motivated. They earn higher grades, according to the study's findings. The students who choose to learn utilizing online tools such as OERs need self-motivation, self-sufficiency, and responsibility. The study emphasized proper orientation and training for students and how to best apply the information and knowledge they get through the Internet because it also allows them to engage in non-academic activities.